Influence Social Media Marketing, Content Marketing And Event Marketing Towards Purchase Intention Mediated By Customer Engagement - Nusantara, Muhammad Dharma; Pardede, Ratlan (CV. Publikasi Indonesia, 2023)
The Fast Moving Consumer Good (FMCG) industry, one of Indonesia's main industries which is closely related to the retail sector, and makes a significant contribution to the national economy, especially food and beverages, experienced an increase of 3.6% in the first quarter of 2022. Transformation of the e-commerce business model Currently, it is not only limited to the B2C (business-to-customer) e-commerce business model, but the B2B (business-to-business) e-commerce business model has spread in Indonesia, making it easier for retail businesses to meet their stock needs for goods for sale. In this study, AMOS version 24 was used to process data from 250 respondents and the quota sampling method from five regions and the criteria for respondents using B2B e-commerce applications. The research focuses on looking at the impact of marketing via social media, marketing content and marketing events on customer interests which mediate purchasing intentions. The results showed that marketing via social media and customer presence had a positive and significant effect on purchase intentions, then marketing events had a positive and significant effect on customers. Meanwhile, marketing content and marketing events have no effect on purchase intentions, marketing via social media and marketing content also do not have a positive and significant effect on customers. Meanwhile, the mediating effect of customers is unable to provide a positive and significant influence on marketing via social media and marketing content on the purchase intention of stall or grocery store owners using B2B e-commerce applications.